Perfluoroalkylated substances (PFASs) and legacy persistent organic pollutants (POPs) in halibut and shrimp from coastal areas in the far north of Norway: Small survey of important dietary foodstuffs for coastal communities - Carlsson, Pernilla; Crosse, John D; Halsall, Crispin; Evenset, Anita; Heimstad, Eldbjørg S; Harju, Mikael (Marine pollution bulletin, 2016)
Halibut (Hippoglossus hippoglossus) and shrimps (Pandalus borealis) are regular foodstuffs for communities in northern Norway and important species for the coastal fishing industry. This is the first study to present a comprehensive overview of the contaminant status of these species, with emphasis on unregulated perfluoroalkylated substances (PFAS). The contaminant concentrations were low and within tolerable levels for human dietary exposure. Median Σpolychlorinated biphenyls (PCB) were 4.9 and 2.5ng/g ww for halibut and unpeeled shrimps, respectively. Concentrations of perfluorooctane sulfonate (PFOS) - the most abundant PFASs - were 0.9 and 2.7ng/g ww in halibut and shrimp, respectively. The halibut fillets were dominated by PCBs, which contributed to 50% of the total POPs load, followed by ΣDDTs; 26% and PFASs (18%), whereas shrimps were dominated by PFASs (74%). ΣPBDEs (polybrominated diphenyl ethers) contributed to 1-4% of the total POP load. Local sources are not contributing significantly to the contaminant burden in these species.
Keywords: průzkumy a dotazníky; kontaminace potravin; Flounder; Water Pollutants, Chemical; Fluorocarbons; Fishes; potrava z moře (živočišná); dieta; Alkanesulfonic Acids; vystavení vlivu životního prostředí; lidé; Food Contamination; Polychlorinated Biphenyls; fluorokarbony; polychlorované bifenyly; kyseliny alkansulfonové; Norsko; platýs; Halogenated Diphenyl Ethers; ryby; Surveys and Questionnaires; Norway; zvířata; Animals; halogenované difenylethery; chemické látky znečišťující vodu; Humans; Environmental Exposure; Diet; Seafood